CLINICAL FEATURES OF INFLUENCE OF DIFFERENT GROUPS OF BLEACHING AGENTS IN THE ORAL CAVITY AT DIFFERENT PERIODS AFTER THE END OF THE TREATMENT - Dvornyk, A.V.; Dvornyk V.М.; Vodoriz, Y.Y.; Skripnykov, P.M.; Tkachenko, I.M. (World of Medicine and Biology, 2022)
The purpose of the study was to assess the clinical changes in the oral cavity after using teeth bleaching systems of different compositions. Totally 65 patients were examined. All patients were 20 to 40 years old and had no severe dental and somatic pathology. This clinical study evaluated the effectiveness and side effects of two products for teeth bleaching. The difference in clinical indicators after the bleaching procedure with the selected gels on the microelement structure of oral liquid was detected. We noticed a significant difference in calcium and sodium indices in the oral fluid. Teeth bleaching agents cause tooth sensitivity manifested by changes in the oral fluid viscosity, pH, and the micronutrient composition. Depending on the bleaching agent used, the teeth bleaching procedure should be completed with remineralizing therapy.